Molecular typing by random amplification of polymorphic DNA and M13 southern hybridization of related paired isolates of Aspergillus fumigatus. - Anderson, M; Gull, K; Denning, D (1996)
Three forms of DNA-based typing procedures for Aspergillus fumigatus isolates have been developed over the last five years. The procedures are random amplification of polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) detection, and Southern hybridizations with various repetitive sequence-based probes. Using two of these procedures, we compared 16 selected isolates, grouped into eight pairs on the basis of epidemiology or previously assigned RFLP types. RAPD with four primers (R108, RC08, 2, and 4), including three previously used with A. fumigatus, showed that one primer, R108, gave the best discrimination (8 types). Southern hybridization of total genomic DNA digested with HindIII and probed with the total bacteriophage M13 genome resulted in the highest overall level of discrimination. Combination of the RAPD and Southern hybridization with the previously assigned RFLP types discriminated 10 isolates of 16. Isolates closely linked epidemiologically could not be distinguished from each other. In addition, three pairs of isolates previously unlinked by epidemiology had the same overall types. Two pairs were obtained from the same hospital within 2 years of each other, whereas the third pair were isolated from California and Germany. A full understanding of the epidemiology and ecology of A. fumigatus requires multiple discriminatory typing procedures.